2013
DOI: 10.3390/md11010213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Reveals Proteins Putatively Involved in Toxin Biosynthesis in the Marine Dinoflagellate Alexandrium catenella

Abstract: Alexandrium is a neurotoxin-producing dinoflagellate genus resulting in paralytic shellfish poisonings around the world. However, little is known about the toxin biosynthesis mechanism in Alexandrium. This study compared protein profiles of A. catenella collected at different toxin biosynthesis stages (non-toxin synthesis, initial toxin synthesis and toxin synthesizing) coupled with the cell cycle, and identified differentially expressed proteins using 2-DE and MALDI-TOF-TOF mass spectrometry. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…In addition, RNA and DNA can be extracted simultaneously from the same sample for further analysis. This method has been widely applied in many dinoflagellate species, such as planktonic P. donghaiense [120], PSP toxin-producing A. catenella [121,122,123,124], and YTX-producing Lingulodinium polyedrum [125]. Nevertheless, a few reports have suggested that this method may not produce high-quality results for certain dinoflagellate samples.…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, RNA and DNA can be extracted simultaneously from the same sample for further analysis. This method has been widely applied in many dinoflagellate species, such as planktonic P. donghaiense [120], PSP toxin-producing A. catenella [121,122,123,124], and YTX-producing Lingulodinium polyedrum [125]. Nevertheless, a few reports have suggested that this method may not produce high-quality results for certain dinoflagellate samples.…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
“…Most proteomic studies in the area of algal toxins have focused on PSP toxin biosynthesis in Alexandrium spp. [118,122,123,124,128,129,130,131]. Certain researchers have compared the 2-DE profiles of 2 strains with considerable variations in the levels of toxins triggered by different environmental conditions or growth phases [124,129,130].…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researches on PSTs as well as dinoflagellates became widely executed in the last few decades with different focus. Proteomics is a new research tool in studying dinoflagellates, and has been widely used in recent years (Chan et al 2002(Chan et al , 2004(Chan et al , 2006Wang et al 2013;Huang et al 2015). The combination of two-dimensional electrophoresis (2-DE) and mass spectrometry analysis works effectively in proteomics studies on dinoflagellates (Chan et al 2002) and other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…These different transcriptomic analyses of Alexandrium species have recently been enriched by a comparative proteomic approach to directly identify proteins potentially involved in STX biosynthesis in A. catenella (Wang et al, 2013). To conduct these experiments, algae were sampled at different stages of toxin biosynthesis (no toxin synthesis, initial toxin synthesis, and toxin-synthesizing).…”
Section: Molecular Bases Of Dinoflagellate Saxitoxin Productionmentioning
confidence: 99%